Application of the Five-Soul Philosophy of Values in Forming Responsive and Active Individuals in Anticipating the Covid 19 Outbreak - Lahmuddin Lahmuddin; Sri Ngayomi Yudha Wastuti; Jamila Jamila (ABDI SABHA (Jurnal Pengabdian kepada Masyarakat), 2021)
The purpose of this article is to provide information about the role of the five souls in each individual who lives side by side in the face of the pandemic and the spread of the Covid-19 outbreak and crisis situations to form a person who is responsive and actively follows all provisions for the safety of the souls of themselves and others. This article was created with a literacy study method from various media sources collected during the pandemic period which can be used as a guide in the guidance and counseling services used by Guidance and Counseling teachers in dealing with crisis situations during the pandemic and the Covid-19 outbreak. The target of this service research is to provide training for PAUD teachers to be able to train students to be responsive and responsive and to be able to get used to complying with health protocols and train themselves to maintain cleanliness carried out by the Muhammadiyah University of North Sumatra to PAUD teachers and students in development programs. kemuhammadiyahan in partnership with PAUD Al-Hasanah and PAUD Rizky.